Student Empowerment SMAN 5 Sigi: Geoliteracy, Local Wisdom, and Disaster Preparedness - Widyastuti, Widyastuti; Novarita, Amalia; Suwarni (Bakti Cendana, 2025)
This literacy empowers communities to devise fitting strategies and actions in line with their specific conditions. Local knowledge-based disaster literacy plays a crucial role during disasters. Consequently, it can decrease disaster impact, raise community resilience, and facilitate recovery in the aftermath. This service aims to assess students' level of geoliteracy about disaster-related information and encourage them to craft disaster education posters informed by local wisdom. This program relies on mentoring and demonstrations, designed to employ clear and accessible language for the students. Implementing geoliteracy services for students at SMA Negeri 5 Sigi, specifically making disaster education posters based on local knowledge, is an effective method to enhance students' comprehension of disaster mitigation while preserving the surrounding culture.